Arthroscopic Management of Osteochondral Lesion of Plantar Medial Talar Head - Lui, Tun Hing (Arthrosc Tech, 2019)
Osteochondral lesions of the talar head can be classified into 4 types: type 1 is located at the anterior part of the talar head, type 2 is at the plantar side of the talar head, type 3 is at the plantar lateral side of the talar head, and type 4 is at the plantar medial aspect of the talar head. The purpose of this Technical Note is to describe the details of arthroscopic management of an osteochondral lesion of the plantar medial talar head. It includes arthroscopic synovectomy of the medial recess of the anterior subtalar joint, debridement, and microfracture of the osteochondral lesion.